The impact of genital psoriasis on quality of life: a systematic review - Yang EJ (Dove Medical Press, 2018)
Eric J Yang,1,2,* Kristen M Beck,1,* Isabelle M Sanchez,1,3 John Koo,1 Wilson Liao1 1Department of Dermatology, University of California San Francisco, San Francisco, CA, USA; 2Chicago Medical School, Rosalind Franklin University of Medicine and Science, North Chicago, IL, USA; 3University of Illinois at Chicago College of Medicine, Chicago, IL, USA *These authors contributed equally to this work Abstract: Psoriasis is a chronic immune-mediated inflammatory disease with significant medical and psychological comorbidities. In addition to having increased cardiovascular risk and mortality, psoriasis patients are more likely to be depressed, anxious, and endorse suicidal ideation than the general population. These patients often have low self-esteem and feel stigmatized due to their skin disease, which can prevent them from pursuing relationships, dating, and attending social activities. Up to 63% of adult psoriasis patients experience psoriatic lesions on their genital area during their lifetime, but often do not discuss these issues with their physicians due to embarrassment, stigmatization, or shyness about this sensitive location. However, psoriasis in sensitive areas, such as the genitals, may result in quality of life impairment greater than that of patients with psoriasis elsewhere on their body, particularly in respect to romantic relationships, intimacy, and sexual function. This article evaluates the current literature regarding the impact of genital psoriasis on the quality of life of affected patients. Keywords: genital psoriasis, quality of life, sexual function, sexual distress, impact